PENGEMBANGAN BUKU CERITA REMAKE SATUA BALI I BELOG BERORIENTASI ERA POSTMODERNISME UNTUK SISWA SD - Ni Made Mili Dwi Cahyani; Putu Nanci Riastini; Ni Putu Kusuma Widiastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Primary school students' interest in Balinese satua has declined due to their limited understanding of the context of historical stories and the dominance of modern reading materials, resulting in local moral and cultural values not being optimally conveyed. This study aims to produce a remake of a Balinese satua storybook entitled I Belog, oriented towards postmodernism, for primary school students, which is reviewed in terms of its design, content validity, and practicality. This study is a research and development study using the ADDIE model. The subject of this study is the remake of the Balinese satua storybook I Belog, oriented towards postmodernism. The developed product was validated by subject matter experts, media experts, and language experts, and was given to primary school teachers and students to obtain feedback on the practicality of the product. The data collection methods used included questionnaires and checklists. The data obtained were analysed using quantitative and qualitative analysis techniques. The results of the content validity test obtained a very high category, with subject matter experts scoring 1, media experts scoring 1, and language experts scoring 0.8. The feasibility of the learning resource was also assessed from the teachers' responses, which scored 100% with a very good qualification, and the students' response test scored 92.53% with a very good qualification. The implications this study indicate that the I Belog remake storybook can strengthen students' cultural literacy and character building if supported by collaboration between schools and the government to integrate traditional values into a modern context